Pengaruh Model Pembelajaran Elaborasi terhadap Hasil Belajar Matematika - Heriyati Heriyati (SAP (Susunan Artikel Pendidikan), 2017)
The aim of this research is to show the effect of the use of elaboration learning model on mathematics learning outcomes. The research uses experiment method, with sample of 30 people taken by employing a simple random sampling technique. The instrument used is a multiple-choice test. The test of comparative hypothesis is conducted using t-test. The result of hypothesis test, namely learning outcomes of students taught using elaboration learning model are higher than those of students not taught using elaboration learning model.